Learnings from the BUB: What factors determine the level of institutional trust in the LGUs? - Rosario G. Manasan; Catharine E. Adaro (Philippine Institute for Development Studies (PIDS), 2018)
Institutional trust is one of the key dimensions of trust in society that demonstrates how people perceive institutions and how well they are operating. Building or maintaining institutional trust is of vital importance in democratic societies since negative experiences with government or other institutions may have much more profound effect than positive experiences. Utilizing the data from a PIDS DILG Bottom-up Budgeting study, this paper sought to determine factors that influence the determination of the level of institutional trust of household sample respondents in their respective local government units (LGUs). The study also inquired if the levels of institutional trust can be individually determined for each phase of the BUB process or can be treated as an aggregate of all its phases. Institutional trust, in this study was tackled in using two approaches: institutional performance approach and the social and cultural approach. The institutional performance approach (Newton & Norris, 1999) focuses on the actual performance of government as vital to understanding citizens 'trust in government, while the social and cultural approach essentially claims that individual life situations and experiences create social trust and cooperation, civic mindedness and mutual benefit between individual. Results showed that social capital variable do provide support for the social and cultural approach in explaining the respondents' levels of trust while customer satisfaction on the various public services involving agricultural support rend to affect the levels of trust in the LGUs.
Keywords: 330; Institutional trust; social capital; bottom-up budgeting; LGUs